Marketing digital: o Instagram como meio de influência na decisão de compra do consumidor - Silva, Jonas Eliab dos Santos da (Universidade Federal Rural do Semi-Árido, 2020)
Through an empirical observation, it was noted that the popularization of digital resources, specifically the Instagram application, could be associated with changing consumer behavior over the years. With the frequent presence of the consumer in the digital environment, the importance of studying the behavior and perception of companies on the subject was realized. The present work was developed with a focus on digital marketing, with the objective of analyzing digital communication on Instagram and the insertion of this new marketing model, gathering knowledge about how companies can use Instagram to benefit, identifying the influence that advertising on social networks have on the online consumer, with the research problem: What is the influence of Instagram on the consumer's purchase decision? The methodology used in this work was descriptive research with a quantitative approach, performing a data collection with a questionnaire, in the cities of Ipanguaçu RN and Angicos RN, being the main research object, the users of the social network Instagram. Data analysis was performed using the tabulation of data obtained from the forms filled out by the respondents. The results made it possible to reach a conclusion that the appearance of the application and, consequently, the rapprochement relationship between the customer and the company, changed the requirements of this consumer in relation to the offered product, remodeling the current market scenario. It also found that the protagonism and the growing criticality of the consumer generated a strategic repositioning of the companies, as other criteria besides the attendance and the quality of the product and started to be considered.
Monografia
Keywords: Marketing digital; Instagram; Redes sociais; Comunicação; Digital marketing; Instagram; Social media; Communication; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::SISTEMAS DE INFORMACAO